Daratumumab for the Treatment of Multiple Myeloma - Plesner, Torben; Krejcik, Jakub (Frontiers in Immunology, 2018)
This mini-review will summarize the present state of development of the CD38 antibody daratumumab for treatment of multiple myeloma.